EU11 Regular Economic Report, Issue #27, June 2013 - World Bank (Washington, DC, 2014)
This economic report covers economic developments, prospects, and policies in 11 European Union (EU) countries. Throughout the report this group of eleven countries is referred to as EU11.The economic recovery of the EU11 countries was put on hold in 2012 as the external environment weakened and domestic demand subsided. All EU11 countries, with the exception of Latvia, grew slower than in 2011. The overall Gross domestic product (GDP) growth of 0.8 percent in 2012 was just a quarter of the pace recorded the year before. Domestic demand, in particular investment, abated, leaving net exports as the sole driver of growth. In addition, the number of EU11 countries in recession doubled to four, after the Czech Republic and Hungary joined Slovenia and Croatia. Overall, this empirical result confirms that, in qualitative terms, the analyzed firm characteristics affect job creation both during recessions and economic recoveries. They indicate that the more productive firms tend to be less vulnerable to economic downturns. Accordingly, any type of activities that increase productivity can be expected to reduce the overall exposure of the EU11 economies to recessions and, therefore, should allow firms to compete more successfully with international competitors.